2020
DOI: 10.1038/s41388-020-01572-w
|View full text |Cite|
|
Sign up to set email alerts
|

A novel UBE2T inhibitor suppresses Wnt/β-catenin signaling hyperactivation and gastric cancer progression by blocking RACK1 ubiquitination

Abstract: Dysregulation of the Wnt/β-catenin signaling pathway is critically involved in gastric cancer (GC) progression. However, current Wnt pathway inhibitors being studied in preclinical or clinical settings for other cancers such as colorectal and pancreatic cancers are either too cytotoxic or insufficiently efficacious for GC. Thus, we screened new potent targets from β-catenin destruction complex associated with GC progression from clinical samples, and found that scaffolding protein RACK1 deficiency plays a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…The promoter region with the lowest methylation density (hypomethylated) in HS samples was the multiple myeloma tumour-associated protein 2 ( MMTAG2 ) gene. Luo et al 93 showed that MMTAG2 (also known as C1orf35) is involved in cell growth by promoting cell cycle progression from G1 to S. Overexpression of MMTAG2 results in up-regulation of c-MYC and subsequent accelerated cell proliferation 94 , perhaps revealing a cell survival mechanism activated in low cows. The promoter regions of two histone deacetylases ( HDAC10 , HDAC4 ) were hypermethylated in HS samples from low cows.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter region with the lowest methylation density (hypomethylated) in HS samples was the multiple myeloma tumour-associated protein 2 ( MMTAG2 ) gene. Luo et al 93 showed that MMTAG2 (also known as C1orf35) is involved in cell growth by promoting cell cycle progression from G1 to S. Overexpression of MMTAG2 results in up-regulation of c-MYC and subsequent accelerated cell proliferation 94 , perhaps revealing a cell survival mechanism activated in low cows. The promoter regions of two histone deacetylases ( HDAC10 , HDAC4 ) were hypermethylated in HS samples from low cows.…”
Section: Discussionmentioning
confidence: 99%
“… 55 UBE2T is able to induce ubiquitination of RACK1 at the lysine K172 to enhance its degradation, leading to activation of Wnt/β-catenin and subsequent increase in gastric cancer progression. 56 β-catenin signaling also participates in drug resistance feature of cancer cells. 57 β-catenin is able to stimulate autophagy and mediate temozolomide resistance of glioblastoma.…”
Section: Beta-catenin: Signaling and Cancer Functionmentioning
confidence: 99%
“…UBE2T plays a key role in the ubiquitination of FANCD2 as part of the core FA complex; it also facilitates the assembly of the core FA complex [ 33 ]. Two recent reports described the identification of a UBE2T inhibitor with therapeutic potential [ 21 , 34 ]. The report of Cornwell et al [ 21 ] described a small molecule that specifically inhibited UBE2T/FANCL-induced ubiquitination of FANCD2.…”
Section: Resultsmentioning
confidence: 99%